2010
DOI: 10.1016/j.apmr.2010.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Capacity and Idebenone Intervention in Children and Adolescents With Friedreich Ataxia

Abstract: Objective To determine the effects of idebenone on exercise capacity in children and adolescents with Friedreich’s Ataxia. Design Secondary analysis of a randomized double-blind, placebo controlled, phase II clinical trial. Setting Clinical research center, exercise physiology laboratory. Participants 42 subjects (ages 9–17) with genetically confirmed FA. Intervention Six-month idebenone regimens of approximately 5, 15, and 45 mg/kg/day or placebo. Main Outcome Variables Peak oxygen consumption (peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 43 publications
(47 reference statements)
1
28
0
1
Order By: Relevance
“…Treatment with the antioxidant idebenone may reduce the degree of LV hypertrophy,28 although the clinical significance of this has not yet been evaluated 29. In a placebo-controlled trial in children with FA, treatment with idebenone did not improve exercise capacity 30. Other neuromuscular disorders associated with HCM include myotonic dystrophy, Refsum disease and mutations in lamin-associated protein genes.…”
Section: Classification and Aetiology Of Paediatric Hcmmentioning
confidence: 99%
“…Treatment with the antioxidant idebenone may reduce the degree of LV hypertrophy,28 although the clinical significance of this has not yet been evaluated 29. In a placebo-controlled trial in children with FA, treatment with idebenone did not improve exercise capacity 30. Other neuromuscular disorders associated with HCM include myotonic dystrophy, Refsum disease and mutations in lamin-associated protein genes.…”
Section: Classification and Aetiology Of Paediatric Hcmmentioning
confidence: 99%
“…As recommended by other authors [23]. Caring for individuals with FA, the scales were administered in a single, one-hour session, to minimize the effects of fatigue and thereby maximize accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this treatment had the usual objectives of a physical program in such patients [23][24][25][26]. Specifically, the objective of each physical session was to develop the patients' functional capacity (aerobic capacity, flexibility, upper and lower limb strength, motor coordination and balance).…”
Section: Rehabilitative Treatmentmentioning
confidence: 99%
“…The study found no evidence that idebenone improved exercise capacity relative to placebo. 28 Exercise has been advised for patients with neuromuscular diseases. In 1986 at the Sixth International Congress of Neuromuscular Disease, Perlman described an exercise study where out of the 20 patients participating, all 10 patients with Friedreich ataxia were more likely to improve or stabilize after a 2-year home exercise program.…”
Section: Progress To Date In Friedreich Ataxiamentioning
confidence: 99%